Odpowiedzi

Najlepsza Odpowiedź!
2009-12-16T16:58:47+01:00
X(3x-2)-18x<kwadrat> = 5x(2-3x)+6
3xkwadrat-2x-18xkwadrat=10x-15xkwadrat=6
3xkwadrat-2x-18xkwadrat-10x+15x(kw)=6
-12x=6/-12
x=-1/2

x<kwadrat> - 2x(x-1)/3 = x (x/3 + 1) - 2/3
3x(kw)-6x(kw)+6x=3x(kw)+3x
3x(kw)-6x(kw)+6x-3x(kw)-3x=0
-6x(kw)=0/-6
x(kw)=0/√
x=0


(kw)-kwadrat
10 4 10
x(3x-2)-18x<kwadrat> = 5x(2-3x)+6
3xkwadrat-2x-18xkwadrat=10x-15xkwadrat=6
3xkwadrat-2x-18xkwadrat-10x+15x(kw)=6
-12x=6/-12
x=-1/2

x<kwadrat> - 2x(x-1)/3 = x (x/3 + 1) - 2/3
3x(kw)-6x(kw)+6x=3x(kw)+3x
3x(kw)-6x(kw)+6x-3x(kw)-3x=0
-6x(kw)=0/-6
x(kw)=0/√
x=0